Research progress of extracellular vesicles derived from mesenchymal stem cells in the treatment of neurodegenerative diseases - Shen, Haibin; Chen, Jie; Liu, Meijin; Zhao, Minghong; Hu, Die; Xie, Fangfang; Jin, Qing; Xiao, Dewang; Peng, Zongbo; Qin, Tao; Rao, Dingyu; Huang, Defa (Frontiers in Immunology, 2025)
As the world’s population ages, neurodegenerative diseases are becoming more widely acknowledged as serious global health and socioeconomic issues. Although many resources have been devoted to the research of these illnesses, little progress has been made in the creation of novel diagnostic and therapeutic approaches. Extracellular vesicles (EVs) are released by all cell types and contain proteins, microRNAs, mRNAs, and other biologically active molecules. EVs play an important role in intercellular communication as well as in the regulation of neuroinflammation. Determining the mechanisms by which EVs contribute to the pathogenesis of neurodegenerative diseases will aid in the development of new therapeutic approaches and diagnostic tools. Mesenchymal stem cells (MSCs) have been shown in studies to control immunological responses, promote the growth of new brain connections, promote the production of blood vessels, and heal damaged tissues. There is growing evidence that MSCs’ ability to treat patients is mostly due to the neurotrophic compounds they secrete through EVs. Since their tiny size allows them to pass through biological barriers and reach injured parts of the central nervous system, MSC-derived extracellular vesicles (MSC-EVs) retain many of the therapeutic qualities of their parent MSCs. This review discusses the role of EVs in neurodegenerative diseases and highlights the potential of MSC-EVs in the treatment of neurodegenerative diseases. The paper also examines the challenges that still need to be overcome and the prospects for using MSC-EVs to treat neurodegenerative illnesses.